Low-smoke halogen-free flame-retardant power cable and preparation method thereof

CN122968057APending Publication Date: 2026-10-23LANGFANG XINGHUA CABLE & WIRE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611389176.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]本发明提出一种低烟无卤阻燃电力电缆及其制备方法,解决了相关技术中电力电缆阻燃性不足的问题

Benefits of technology

本发明中,氢氧化铝、氢氧化镁和羟基氧化铝包覆凹凸棒土相互配合,应用于电力电缆护套层中提升了护套层的阻燃性,进而提升电力电缆的阻燃性。氢氧化铝分解温度相对较低,在燃烧初期迅速吸收热量、稀释可燃气体;羟基氧化铝和氢氧化镁的分解温度高于氢氧化铝,形成第二梯度的阻燃;羟基氧化铝包覆凹凸棒土中凹凸棒土表面的羟基氧化铝分解形成氧化铝时,凹凸棒土变成表面含有陶瓷相包覆的支撑骨架充分发挥阻隔效果,三者协同作用,显著提升了电缆护套层的阻燃性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of power cables, and discloses a low-smoke halogen-free flame-retardant power cable and a preparation method thereof. The low-smoke halogen-free flame-retardant power cable comprises, from inside to outside, a conductor, an insulation layer and a sheath layer; the sheath layer comprises the following components in parts by weight: 40-47 parts of polypropylene, 53-60 parts of ethylene-vinyl acetate copolymer, 5-8 parts of a compatilizer, 30-35 parts of a flame retardant, 12-15 parts of a filler and 1-2 parts of a coupling agent; the flame retardant comprises aluminum hydroxide, magnesium hydroxide and modified attapulgite; and the modified attapulgite is attapulgite coated with aluminum oxyhydroxide. The above technical scheme solves the problem of insufficient flame retardancy of the power cable in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable technology, specifically to a low-smoke halogen-free flame-retardant power cable and its preparation method. Background Technology

[0002] Power cables are the core carriers for power transmission and distribution, and are widely laid in various application scenarios, thus placing higher demands on their safety.

[0003] Fires caused by aging circuits pose a potential safety hazard during cable use. Current research largely focuses on improving the flame-retardant properties of cables by adding flame retardants, but the flame-retardant effect remains unsatisfactory. In a fire, the sheath layer easily melts and rapidly detaches, failing to form a continuous and dense char layer to block flame and heat transfer. This allows the fire to spread along the cable, and the released flammable gases further exacerbate the fire's spread, making it difficult to meet flame-retardant requirements. Therefore, there is an urgent need to develop power cables with highly efficient flame-retardant properties. Summary of the Invention

[0004] This invention proposes a low-smoke halogen-free flame-retardant power cable and its preparation method, which solves the problem of insufficient flame retardancy of power cables in related technologies.

[0005] The technical solution of the present invention is as follows: This invention proposes a low-smoke halogen-free flame-retardant power cable, which comprises, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 40-47 parts polypropylene, 53-60 parts ethylene-vinyl acetate copolymer, 5-8 parts compatibilizer, 30-35 parts flame retardant, 12-15 parts filler, and 1-2 parts coupling agent. The flame retardant includes aluminum hydroxide, magnesium hydroxide, and modified attapulgite. The modified attapulgite is attapulgite coated with alumina hydroxyl oxide.

[0006] As a further technical solution, the mass ratio of aluminum hydroxide, magnesium hydroxide, and aluminum hydroxide coated attapulgite is 2:1:0.15~0.25.

[0007] In the sheath layer of this invention, when the flame retardant is aluminum hydroxide, magnesium hydroxide, and aluminum hydroxide in a mass ratio of 2:1:0.15~0.25 coating attapulgite, the flame retardant properties of the resulting sheath layer are more excellent. When the amount of aluminum hydroxide coating attapulgite is too small, its flame retardant and barrier effects are insufficient. When the amount of aluminum hydroxide coating attapulgite is too large, the amount of aluminum hydroxide and magnesium hydroxide added is relatively reduced, resulting in a decrease in flame retardant performance.

[0008] As a further technical solution, the sheath layer also includes the following components in parts by weight: 1.4 to 2 parts antioxidant, 0.7 to 1 part ultraviolet absorber, and 0.8 to 2 parts lubricant.

[0009] As a further technical solution, the preparation process of the hydroxyalumina-coated attapulgite includes the following steps: S1. Add attapulgite clay to aluminum chloride solution, stir, add alkali solution, and obtain suspension; S2. Stir, settle, filter, wash and dry the suspension to obtain hydroxyalumina-coated attapulgite.

[0010] As a further technical solution, the concentration of the aluminum chloride solution is 0.074~0.075 mol / L.

[0011] As a further technical solution, the mass-to-volume ratio of the attapulgite clay and the aluminum chloride solution is 5g:180~200mL.

[0012] As a further technical solution, in step S1, the stirring temperature is 25°C, the stirring speed is 150~200 rpm, and the stirring time is 20~30 min.

[0013] As a further technical solution, the alkaline solution is a sodium hydroxide solution.

[0014] As a further technical solution, the concentration of the sodium hydroxide solution is 1 mol / L.

[0015] As a further technical solution, the pH of the suspension is 7.

[0016] As a further technical solution, in step S2, the stirring speed is 150~200 rpm and the time is 5.5~6.5 h.

[0017] As a further technical solution, the settling time is 10~12h.

[0018] As a further technical solution, the drying temperature is 60~70℃ and the time is 10~12h.

[0019] As a further technical solution, the polypropylene includes random copolymer polypropylene and homopolymer polypropylene with a mass ratio of 2 to 3:1.

[0020] Preferably, the mass ratio of random copolymer polypropylene to homopolymer polypropylene is 7:3.

[0021] In the sheath layer of this invention, the polypropylene is a combination of random copolymer polypropylene and homopolymer polypropylene, which can further improve the flame retardant performance of the cable sheath layer. The matrix formed by the random copolymer polypropylene and homopolymer polypropylene can better disperse the flame retardant in the sheath layer, allowing each to exert its flame retardant effect more fully, improving flame retardant efficiency, and significantly enhancing the flame retardancy of the power cable sheath layer. The mass ratio of random copolymer polypropylene to homopolymer polypropylene can be 8:4, 7:3, and 6:2.

[0022] As a further technical solution, the melt index of the ethylene-vinyl acetate copolymer at 190°C and 2.16 kg is 2.5 g / 10 min.

[0023] As a further technical solution, the melt index of the random copolymer polypropylene at 230℃ and 2.16kg is 2.1g / 10min.

[0024] As a further technical solution, the homopolymer polypropylene has a melt index of 2.8 g / 10 min at 230°C and 2.16 kg.

[0025] As a further technical solution, the compatibilizer includes maleic anhydride-grafted polypropylene.

[0026] As a further technical solution, the filler includes one of talc powder and kaolin.

[0027] In the sheath layer of the present invention, the addition of filler can improve the overall mechanical properties of the material; the filler can be one or more of the conventional fillers in the art, such as talc, kaolin, calcium carbonate, etc., preferably, the filler is one of talc and kaolin.

[0028] As a further technical solution, the coupling agent includes a silane coupling agent.

[0029] As a further technical solution, the antioxidant includes one or both of antioxidant 1010 and antioxidant 1076.

[0030] In the sheath layer of the present invention, the addition of an antioxidant can inhibit the oxidation reaction of the polymer material; the antioxidant can be one or more of the conventional antioxidants in the art, such as antioxidant 1010, antioxidant 1076, antioxidant 1098, etc., preferably, the antioxidant is one or two of antioxidant 1010 and antioxidant 1076.

[0031] As a further technical solution, the ultraviolet absorber includes ultraviolet absorber UV-531.

[0032] As a further technical solution, the lubricant includes one of polyethylene wax and zinc stearate.

[0033] This invention also proposes a method for preparing a low-smoke halogen-free flame-retardant power cable, comprising the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; the sheath layer mixture is then extruded over the semi-finished power cable to obtain a low-smoke halogen-free flame-retardant power cable.

[0034] The working principle and beneficial effects of this invention are as follows: In this invention, aluminum hydroxide, magnesium hydroxide, and aluminum hydroxide coating on attapulgite work synergistically and are applied to the sheath layer of power cables to enhance the flame retardancy of the sheath layer, thereby improving the flame retardancy of the power cables. Aluminum hydroxide has a relatively low decomposition temperature, rapidly absorbing heat and diluting flammable gases in the early stages of combustion. Aluminum hydroxide and magnesium hydroxide have higher decomposition temperatures than aluminum hydroxide, forming a second-gradient flame retardancy. When the aluminum hydroxide on the surface of the attapulgite decomposes to form aluminum oxide, the attapulgite becomes a supporting skeleton with a ceramic phase coating, fully exerting its barrier effect. The synergistic effect of these three components significantly improves the flame retardant performance of the cable sheath layer. Detailed Implementation

[0035] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0036] In the following examples and comparative examples, attapulgite: particle size 2000 mesh; polyethylene wax: AC 6A; talc: particle size 2000 mesh; kaolin: particle size 2000 mesh; ethylene-vinyl acetate copolymer: melt index (190℃ / 2.16kg) 2.5g / 10min, ExxonMobil. TM EVA 2503.NF; Random copolymer polypropylene: melt index (230℃ / 2.16kg) is 2.1g / 10min, model is ExxonMobil™ PP9152; Homopolymer polypropylene: melt index (230℃ / 2.16kg) is 2.8g / 10min, model is ExxonMobil TM PP6292NE1; Maleic anhydride-grafted polypropylene: model number 50E739.

[0037] Example 1 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 40 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 60 parts ethylene-vinyl acetate copolymer, 5 parts maleic anhydride grafted polypropylene, 30 parts flame retardant, 15 parts talc, 1 part silane coupling agent KH-550, 1.4 parts antioxidant 1010, 0.7 parts ultraviolet absorber UV-531, and 0.8 parts polyethylene wax; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.1; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.074 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 150 rpm for 30 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 150 rpm for 6.5 h, settled for 10 h, filtered, washed, dried at 60 ℃ for 12 h, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0038] Example 2 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 47 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 53 parts ethylene-vinyl acetate copolymer, 8 parts maleic anhydride grafted polypropylene, 35 parts flame retardant, 12 parts kaolin, 2 parts silane coupling agent KH-550, 2 parts antioxidant 1076, 1 part ultraviolet absorber UV-531, and 2 parts zinc stearate; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.1; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 180 mL), and stirred at 25 °C and 200 rpm for 20 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 200 rpm for 5.5 h, settled for 12 h, filtered, washed, dried at 70 ℃ for 10 h, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0039] Example 3 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.1; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0040] Example 4 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.15; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0041] Example 5 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.25; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0042] Example 6 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is attapulgite clay coated with aluminum hydroxide, magnesium hydroxide and aluminum hydroxide in a mass ratio of 2:1:0.3; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0043] Example 7 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 7:3), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.25; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0044] Example 8 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 3:1), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.25; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0045] Example 9 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts random copolymer polypropylene, 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.25; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0046] Example 10 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts homopolymer polypropylene, 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:1:0.25; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0047] Comparative Example 1 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide and magnesium hydroxide in a mass ratio of 2:1; A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0048] Comparative Example 2 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is aluminum hydroxide and aluminum hydroxide coated with attapulgite in a mass ratio of 2:0.1; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0049] Comparative Example 3 A low-smoke halogen-free flame-retardant power cable, comprising, from the inside out, a conductor, an insulation layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 43 parts polypropylene (random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2:1), 57 parts ethylene-vinyl acetate copolymer, 6 parts maleic anhydride grafted polypropylene, 32 parts flame retardant, 14 parts talc, 1.5 parts silane coupling agent KH-550, 0.6 parts antioxidant 1010, 0.4 parts antioxidant 1076, 0.8 parts ultraviolet absorber UV-531, and 1.5 parts polyethylene wax; The flame retardant is attapulgite clay coated with magnesium hydroxide and aluminum hydroxide in a mass ratio of 1:0.1; The preparation process of hydroxyalumina-coated attapulgite includes the following steps: Attapulgite was added to an aluminum chloride solution with a concentration of 0.075 mol / L (the mass-volume ratio of attapulgite to aluminum chloride solution was 5 g: 200 mL), and stirred at 25 °C and 180 rpm for 25 min. A sodium hydroxide solution with a concentration of 1 mol / L was then added dropwise at a dropping rate of 0.05 mL / drop to obtain a suspension with a pH of 7. The suspension was stirred at 180 rpm for 6 hours, settled for 12 hours, filtered, washed, dried at 65℃ for 11 hours, and ground to obtain hydroxyalumina-coated attapulgite with a particle size of 2000 mesh. A low-smoke halogen-free flame-retardant power cable includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; a sheathing mixture is then extruded over the semi-finished power cable to obtain a low-smoke, halogen-free, flame-retardant power cable.

[0050] Experimental Example 1 The oxygen index of the sheathing layers of the low-smoke halogen-free flame-retardant power cables prepared in Examples 1-10 and Comparative Examples 1-3 was tested according to the method specified in GB / T2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test". Type IV specimens were selected, and Method A was used for ignition. The test results are shown in Table 1. Table 1 Performance test of the sheath layer of low-smoke halogen-free flame-retardant power cables prepared in Examples 1-10 and Comparative Examples 1-3

[0051] 1. Compared with Comparative Examples 1 to 3, the oxygen index of the sheath layer of the low-smoke halogen-free flame-retardant power cable prepared in Examples 1 to 10 is higher than that in Comparative Examples 1 to 3. This indicates that the coating of attapulgite with aluminum hydroxide, magnesium hydroxide and aluminum hydroxide as flame retardants can significantly improve the flame retardancy of the sheath layer of the low-smoke halogen-free flame-retardant power cable.

[0052] 2. Compared with Examples 3 to 6, the oxygen index of the sheath layer of the low-smoke halogen-free flame-retardant power cable prepared in Examples 4 to 5 is higher than that in Examples 3 and 6. This indicates that adjusting the mass ratio of aluminum hydroxide, magnesium hydroxide and aluminum hydroxide coated attapulgite in the range of 2:1:0.15 to 0.25 can further improve the flame retardancy of the sheath layer of the low-smoke halogen-free flame-retardant power cable.

[0053] 3. Compared with Examples 5 and 7-10, the oxygen index of the sheath of the low-smoke halogen-free flame-retardant power cable prepared in Example 7 is significantly higher than that in Examples 5 and 8-10. This indicates that when the polypropylene is random copolymer polypropylene and homopolymer polypropylene with a mass ratio of 7:3, the flame retardancy of the sheath of the low-smoke halogen-free flame-retardant power cable is significantly improved.

[0054] Experimental Example 2 The maximum specific optical density of the sheath layer of the low-smoke halogen-free flame-retardant power cables prepared in Examples 1-3 was tested according to the method specified in GB / T 8323.2-2008 "Plastic Smoke Generation Part 2: Test Method for Determination of Smoke Density by Single Chamber Method". The sample size was 75mm×75mm×25mm, and the irradiance at the sample was 25kW / m². 2 The test results are shown in Table 2: Table 2 Test results of the sheath layer of the low-smoke halogen-free flame-retardant power cables prepared in Examples 1-3

[0055] As shown in Table 2, the maximum specific optical density of the sheath layer of the low-smoke halogen-free flame-retardant power cables prepared in Examples 1-3 is ≤140%.

[0056] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A low-smoke halogen-free flame-retardant power cable, characterized in that, From the inside out, it consists of a conductor, an insulating layer, and a sheath layer; The sheath layer comprises the following components in parts by weight: 40-47 parts polypropylene, 53-60 parts ethylene-vinyl acetate copolymer, 5-8 parts compatibilizer, 30-35 parts flame retardant, 12-15 parts filler, and 1-2 parts coupling agent. The flame retardant includes aluminum hydroxide, magnesium hydroxide, and modified attapulgite. The modified attapulgite is attapulgite coated with alumina hydroxyl oxide.

2. The low-smoke halogen-free flame-retardant power cable according to claim 1, characterized in that, The mass ratio of aluminum hydroxide, magnesium hydroxide, and aluminum hydroxide-coated attapulgite is 2:1:0.15~0.

25.

3. The low-smoke halogen-free flame-retardant power cable according to claim 1, characterized in that, The sheath layer also includes the following components in parts by weight: 1.4 to 2 parts antioxidant, 0.7 to 1 part ultraviolet absorber, and 0.8 to 2 parts lubricant.

4. The low-smoke halogen-free flame-retardant power cable according to claim 1, characterized in that, The preparation process of the hydroxyalumina-coated attapulgite includes the following steps: S1. Add attapulgite clay to aluminum chloride solution, stir, add alkali solution, and obtain suspension; S2. Stir, settle, filter, wash and dry the suspension to obtain hydroxyalumina-coated attapulgite.

5. A low-smoke halogen-free flame-retardant power cable according to claim 4, characterized in that, The concentration of the aluminum chloride solution is 0.074~0.075 mol / L; The mass-to-volume ratio of the attapulgite clay and the aluminum chloride solution is 5g:180~200mL; The pH of the suspension is 7.

6. A low-smoke halogen-free flame-retardant power cable according to claim 4, characterized in that, In step S2, the stirring speed is 150~200 rpm, and the time is 5.5~6.5 h; The settling time is 10-12 hours.

7. The low-smoke halogen-free flame-retardant power cable according to claim 1, characterized in that, The polypropylene includes random copolymer polypropylene and homopolymer polypropylene in a mass ratio of 2 to 3:

1. The ethylene-vinyl acetate copolymer has a melt index of 2.5 g / 10 min at 190 °C and 2.16 kg. The random copolymer polypropylene has a melt flow index of 2.1 g / 10 min at 230 °C and 2.16 kg. The homopolymer polypropylene has a melt flow index of 2.8 g / 10 min at 230°C and 2.16 kg.

8. The low-smoke halogen-free flame-retardant power cable according to claim 1, characterized in that, The compatibilizer comprises maleic anhydride-grafted polypropylene. The filler includes one of talc powder and kaolin. The coupling agent includes a silane coupling agent.

9. A low-smoke halogen-free flame-retardant power cable according to claim 1, characterized in that, The antioxidant includes one or both of antioxidant 1010 and antioxidant 1076; The ultraviolet absorber includes ultraviolet absorber UV-531; The lubricant includes one of polyethylene wax and zinc stearate.

10. A method for preparing a low-smoke halogen-free flame-retardant power cable, used to prepare the low-smoke halogen-free flame-retardant power cable according to any one of claims 1 to 9, characterized in that, Includes the following steps: The components of the sheath layer are mixed to obtain the sheath layer mixture; An insulation layer is extruded over the conductor to obtain a semi-finished power cable; the sheath layer mixture is then extruded over the semi-finished power cable to obtain a low-smoke halogen-free flame-retardant power cable.